# Example 1 Solve ax b c for x. Then use the solution to solve Solve a literal equation + = += 2x 5 11. SOLUTION STEP 1 Solve ax b c for x. += ax b c Write.

## Presentation on theme: "Example 1 Solve ax b c for x. Then use the solution to solve Solve a literal equation + = += 2x 5 11. SOLUTION STEP 1 Solve ax b c for x. += ax b c Write."— Presentation transcript:

Example 1 Solve ax b c for x. Then use the solution to solve Solve a literal equation + = += 2x 5 11. SOLUTION STEP 1 Solve ax b c for x. += ax b c Write original equation. + = = bc a – x Assume a 0. Division property of equality = Subtraction property of equality ax– = c b

Example 1 Solve a literal equation STEP 2 Use the solution to solve 2x 5 11. += Solution of literal equation = bc a – x 3= Simplify. Substitute 2 for a, 5 for b, and 11 for c. = 511 2 – ANSWER The solution of 2x 5 11 is 3. +=

Guided Practice for Example 1 Solve the literal equation for x. Then use the solution to solve the specific equation. 1. a bx c ; 12 5x 3 – – = – = 2. ax bx c ; 11x 6x 20 =+= + ANSWER = ca b – x ; 3; 3 = ba c x – ; 4; 4

Download ppt "Example 1 Solve ax b c for x. Then use the solution to solve Solve a literal equation + = += 2x 5 11. SOLUTION STEP 1 Solve ax b c for x. += ax b c Write."

Similar presentations